Ilmu Lingkungan sebagai Jembatan Penerapan Tuntutan Qur'an dan Sunnah - Dradjat Suhardjo (Unisia, 2005)
Environmental science is the holder of the almost science, it be redifined as a paradigm to solve ofenvironmental problem. All men are created equal by they Creator as the leader of the global ecosystem. They responsible about global ecosystem condition as earner of the lifing. The natural of human character is negative and positive behavior. The negative behavior as distroyer be influenced by poor, stupid and immoral condition. The otherside as the guard of global function will be full filed if the welfare, responsibility and morality as way of life of the leader.